SAMURAI-S: Sonic Anemometer on a MUlti-Rotor drone for Atmospheric turbulence Investigation in a Sling load configuration - Ghirardelli, Mauro; Kral, Stephan T.; Cheynet, Etienne; Reuder, Joachim (Atmospheric measurement techniques, 2025)
This study introduces the SAMURAI-S, a novel measurement system that incorporates a state-of-the-art sonic anemometer combined with a multi-rotor drone in a sling load configuration, designed to overcome the limitations of traditional mast-based observations in terms of spatial flexibility. This system enables the direct measurement of 3D wind vectors while hovering, providing a significant advantage in manoeuvrability and positional accuracy over fixed mast setups. The capabilities of the system were quantified through a series of 10 to 28 min flights, conducting close comparisons of turbulence measurements at altitudes of 30 and 60 m against data from a 60 m tower equipped with research-grade sonic anemometers. The results demonstrate that SAMURAI-S matches the data quality of conventional setups for horizontal wind measurements while slightly overestimating vertical turbulence components. This overestimation increases with wind speed.